Haha du er skør… og sød: En undersøgelse af komplimenter og flirten i sms’er - Nielsen, Eva Hellesøe (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2018)
The main subjects of this study are compliments and flirtation in written discourse. The data of the paper are text messages that two young women exchanged while dating during a period of two and a half months. Since there are more than a thousand messages, two weeks have been selected for this analysis. To examine the data, the method of conversation analysis has been used, in particular compliment theory. Compliments differ from other actions in as much as agreement and accept are not the preferred actions to follow since self-praise is dispreferred. Theories of flirtation are presented as well, and the notion of imagined togetherness. Five extracts of the data are analysed, focusing on relevant characteristics and phenomena of each extract, such as imagined togetherness, compliment structure, irony and emojis. The paper concludes that compliments are exchanged within sequences that also contain everyday subjects; and features such as suspension dots and emojis play a crucial part in the understanding and interpretation of the messages.